2018
DOI: 10.1139/cjps-2017-0342
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of precision agriculture technologies in Ontario crop production

Abstract: Ontario agricultural service providers were surveyed on their use of precision agricultural technologies. Global positioning systems are the most commonly adopted, while adoption rates for variable rate systems are significantly less. Enhancing adoption requires turning the vast amount of data collected on crop production into valuable decisions for the farmer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…markets, policies), and producer perceptions (e.g. perceptions about profitability, environmental benefits) as the major determinants of PAT adoption in general (Pierpaoli et al 2013;Tey and Brindal 2012;Mitchell et al 2018;Paustian and Theuvsen 2017;Reichardt and Jürgens 2009;Robertson et al 2012;Tamirat et al 2018;Isgin et al 2008;Lambert et al 2015;Roberts et al 2004). However, studies on the adoption determinants of popular…”
Section: Variable Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…markets, policies), and producer perceptions (e.g. perceptions about profitability, environmental benefits) as the major determinants of PAT adoption in general (Pierpaoli et al 2013;Tey and Brindal 2012;Mitchell et al 2018;Paustian and Theuvsen 2017;Reichardt and Jürgens 2009;Robertson et al 2012;Tamirat et al 2018;Isgin et al 2008;Lambert et al 2015;Roberts et al 2004). However, studies on the adoption determinants of popular…”
Section: Variable Selectionmentioning
confidence: 99%
“…Studies from the United States, Canada, Australia, and the EU show that PAT adoption varies by technology type and region/countries (Griffin et al 2004;Erickson et al 2017;Miller et al 2019;Mitchell et al 2018;Robertson et al 2012;Tamirat et al 2018;Michels et al 2020;Paustian and Theuvsen 2017). Some studies show that adoption rates of information-intensive PATs are lower than those of embodied-knowledge PATs (Miller et al 2019;Erickson et al 2017;Mitchell et al 2018;Robertson et al 2012;Bramley and Ouzman 2019;Bullock and Lowenberg-DeBoer 2007). For example, auto guidance was used in 59% of crop area planted to corn in the United States in 2016, and by 77% of grain growers in Australia in 2012, whereas variable-rate technology (VRT) fertilizer was used in 29% of crop area planted to corn in the United States in 2016 and among 49% of grain growers in Australia in 2012 (Lowenberg-DeBoer and Erickson 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, uptake has been unexpectedly slow, so the application provides an opportunity to assess the range of factors affecting adoption (Mitchell et al . ). The role of economic as well as other factors in the adoption process based on previous studies is then summarized.…”
Section: Introductionmentioning
confidence: 97%
“…The digital revolution, allowing the rate of fertilizer to vary spatially across the field in contrast to the traditional approach of a single uniform rate, has the potential to increase net returns while concurrently reducing the sector's environmental impact ). However, uptake has been unexpectedly slow, so the application provides an opportunity to assess the range of factors affecting adoption (Mitchell et al 2018). The role of economic as well as other factors in the adoption process based on previous studies is then summarized.…”
Section: Introductionmentioning
confidence: 99%
“…In a review of studies examining the factors affecting adoption all of which were conducted in the US and EU, Pathak et al (2019) found farm size and farmer education were the common determinants regardless of the type of precision agriculture considered. Recent Canadian studies include Mitchell et al (2018) and Steele (2018) while Turland and Slade (2020) examined the willingness of farmers to participate in Big Data platforms but not the adoption of the associated technologies. To assess adoption barriers, it is important to understand farmers' perceptions of the benefits, which can be multi-faceted and differ along the adoption process (Weersink and Fulton, 2020;Thompson et al 2019).…”
Section: Introductionmentioning
confidence: 99%